K- and Cu-doped CaTiO3-based nanostructured hollow spheres as alternative catalysts to produce fatty acid ethyl esters as potential biodiesel - Lanfredi, S. [UNESP]; Matos, J.; da Silva, S. R. [UNESP]; Djurado, E.; Sadouki, A. S.; Chouaih, A.; Poon, P. S.; González, E. R.P. [UNESP]; Nobre, M. A.L. [UNESP] (Elsevier, 2020)
New functional polycation oxide-type catalysts were synthesized by the ultrasonic spray-pyrolysis method. The catalytic activity in the production of fatty acid ethyl esters (FAEE's) using soybean oil was studied. Catalysts are conformed by nanostructured hollow spheres of low density with a stoichiometric formula Ca1-xKxTiCux/2O3. The influence of the substitutional ratio (x) upon the catalytic activity was verified. The Ca1-xKxTiCux/2O3 sample with x = 0.3 showed the highest activity with a yield up to 89 % to produce fatty acid ethyl esters (FAEE's) after 24 h reaction using 15 wt.% catalysts, 120 °C and 40 bars. The enhancement in the activity was ascribed to the substitution of the Ca+2 sites by K+ and Ti+4 by Cu+2 and to the hollow morphology favoring a more effective interaction between the soybean oil and the active basic sites of the catalysts.
Keywords: CaTiO3-based catalysts; FAEE's synthesis; Hollow spheres; K- and Cu-doping; Ultrasonic Spray Pyrolysis